Exon 1 deletion of the androgen receptor gene causing complete androgen insensitivity syndrome in a newborn: a case report - Wang, Shengxia; Zhang, Ya-Ting; Wang, Fan (Frontiers in Pediatrics, 2025)
ObjectiveTo genetically characterize a case of neonatal complete androgen insensitivity syndrome (CAIS) and identify the underlying molecular defect.MethodsThis was a retrospective analysis of the clinical data, diagnosis, and treatment of a case of CAIS in the Second Hospital of Lanzhou University. Genetic testing of the patient and their parents was done; the pathogenic genes of the child were detected using whole exome sequencing (WES) technology.ResultsThe social sex of the proband was female, but the chromosomal sex was male. WES detected Exon 1 deletion mutation of AR gene in the proband and Exon 1 heterozygosity deletion in the mother. This mutation may cause disease according to the ACMG guidelines, but this variation has not been reported in CAIS caused by an AR gene.ConclusionThis study genetically characterized a neonate with CAIS, identifying a novel Exon 1 deletion in the AR gene as the underlying cause. This finding expands the spectrum of known mutations associated with CAIS and provides valuable insights into the genetic basis of this condition.